Stacking methods and lumber quality of Eucalyptus dunnii and Araucaria angustifolia after air drying - Dittmann, Raquel Luiza; de Souza, Joel Telles; Talgatti, Maiara; Baldin, Talita; de Menezes, Walmir Marques (Scientia Agraria Paranaensis, 2017)
The purpose of the current study was to evaluate the lumber quality of Eucalyptus dunnii and Araucaria angustifolia thereupon air drying, in two different methods of stacking, traditional and triangular. To this purpose, 120 boards were used, being 60 for each species. The material was manipulated in a lumberyard, located in municipality of Xanxerê, Santa Catarina State, Brazil. It was stacked in the traditional and triangular way, with 30 boards for each repetition. The boards had length dimensions of 150 cm, width of 15 to 35 cm and thickness of 2.5 cm. The boards quality analysis was based on the evaluation of warping defects, after the pit sawing and the end of drying by the biggest arrow, in mm. Additionally, it was verified the presence of top cracks, collapse and knots, both a priori and a posteriori. No significant difference was observed between the traditional and the triangular methods for both species, indicating that the form of stacking did not have influence in the wood quality. A. angustifolia samples presented better condition for air-drying, thereby, the boards had lower defect rate, however, in this species; the knots rate was significantly higher compared to eucalyptus. E. dunnii samples, even with higher defect numbers, presented lower knots number. No breakdown was evidenced on the boards of both species during drying, reinforcing the stacking quality.